Experimental validation of indoor relay-assisted visible light communications for a last-meter access network - Pesek, Petr; Zvanovec, Stanislav; Chvojka, Petr; Ghassemlooy, Zabih; Mohd Nor, Norhanis Aida; Tabeshmehr, Pooria (Elsevier, 2019)
This paper provides experimental results for a relay-assisted visible light communications (VLC) link using a white light-emitting diode (LED) for a last-meter access network. We demonstrate that a relay-based VLC scheme improves the system performance, especially for link spans longer than 5 meters, in the presence of blocking and shadowing by redirecting the transmitted signal. We also demonstrate a multiband carrier-less amplitude and phase modulation (m-CAP) VLC link where the decode-and-forward (DF) relay scheme offers improvement in the data rate by 25% and 60% when compared to the amplify-and-forward (AF) relay-based link and single VLC link over a 7 m transmission distance respectively.